Β‐2 Agonists as Misusing Drugs? Assessment of both Clenbuterol‐ and Salbutamol‐related European Medicines Agency Pharmacovigilance Database Reports. Issue 2 (6th April 2018) - Milano, Giulia; Chiappini, Stefania; Mattioli, Francesca; Martelli, Antonietta; Schifano, Fabrizio
Abstract: A recent years' increase in misusing levels of image‐ and performance‐ enhancing drugs (IPEDs) has been observed. Out of these drugs, beta‐2 agonists have recently emerged for their potential of misuse, especially for slimming and bodybuilding purposes. To this perspective, clenbuterol ('the size zero pill') has been reported as being both popular and widely available from the illegal market. All clenbuterol and salbutamol misuse/abuse/dependence/withdrawal/overdose/off‐label spontaneous reports (2006–2016) from the European Medicines Agency (EMA) EudraVigilance (EV) database were collected and analysed by age range, gender, concomitant therapies and source of information. From the EV database, 55 of a total number of 920 'suspect' misuse/abuse/dependence/withdrawal/overdose/off‐label ADRs (e.g. 5.97%; corresponding to 25 of 138 individuals) and 1310 of 62, 879 ADRs (e.g. 2.08%; corresponding to 474 of 6923 individuals) were, respectively, associated with clenbuterol (typically ingested in combination with a range of anabolic steroids) and salbutamol. Proportional reporting ratio (PRR) value for misuse/abuse ADRs was higher (PRR = 18.38) for clenbuterol in comparison with salbutamol. Clenbuterol misuse/abuse could be a cause for major concern, especially in vulnerable individuals.